Prenatal exposure to betamethasone causes intergenerational impairment of epididymal development in the rat. (27th June 2019) - Kempinas, W. G.; Borges, C. S.; Leite, G. A. A.; Figueiredo, T. M.; Gregory, M.; Cyr, D. G.
Abstract: Background: Studies on epididymal toxicology are scarce. Betamethasone (BM) is a glucocorticoid used in clinical practice for antenatal therapy. We previously reported changes to testicular morphology, altered sperm quality, and fertility in adult rats following intrauterine administration of BM. Objectives: Given that high levels of corticosteroids during gestation lead to fetal androgen depletion, and the essential role of testosterone during epididymal development, here we investigated epididymal morphology and physiology in the F1 and F2 male offspring of female rats treated with BM during gestation. Materials and methods: Pregnant rats were randomly divided into two experimental groups: control (saline vehicle, n = 11) and BM‐treated group (0.1 mg/kg betamethasone 21‐phosphate disodium, n = 13). Rats received an intramuscular injection of vehicle or BM on gestational days 12, 13, 18, and 19. This encompasses the beginning of the critical window of male rat reproductive tract development. A subset of three males from each litter ( n = 5 litters/group) was used: One rat per litter was euthanized at puberty, one was euthanized at adulthood, while the others were mated with a non‐treated female to obtain the F2 generation. The same protocol described for the F1 was applied for F2, except for the mating protocol. Results: In both F1 and F2 generations, prenatal BM exposure resulted in delayed differentiation of the cauda epididymal epithelium, characterized by increased cribriform appearance on PND 45, and displayed weaker or non‐detectable Cx43 immunostaining. Furthermore, in the F1 generation only, immunostaining of TP63, a transcription factor expressed in basal cells, appeared more intense with a greater number of TP63‐positive cells observed in the cauda epididymis. In adults, the epithelial area was reduced in the F1 BM rats. The contractile activity of isolated epididymal ducts was comparable between groups. Discussion and Conclusion: Prenatal BM exposure leads to intergenerational impairment in the development and structure of the rat epididymis.